Complaint! - Ahmed, Sara, 1969- (Duke University Press, 2021)
"In Complaint! Sara Ahmed examines what we can learn about power from those who complain about abuses of power. Drawing on oral and written testimonies from academics and students who have made complaints about harassment, bullying and unequal working conditions at universities, Ahmed explores the gap between what is supposed to happen when complaints are made and what does happen. To make complaints within institutions is to learn how they work and for whom they work: complaint as feminist pedagogy. Ahmed explores how complaints are made behind closed doors and how doors are often closed upon those who complain. To open these doors, to get complaints through, keep them going, or keep them alive, Ahmed emphasizes, requires forming new kinds of collectives. The book offers a systematic analysis of the methods used to stop complaints and a powerful and poetic meditation on what complaints can be used to do. Following a long lineage of Black feminist and feminist of color critiques of the university, Ahmed delivers a timely consideration of how institutional change becomes possible and why it is necessary"--Publisher's description.